Structure, conformational properties and matrix photochemistry of S-(tert-butyl)trifluorothioacetate CF3C(O)SC(CH3)3. (19th August 2020) - Cayón, Vanina M.; Erben, Mauricio F.; Romano, Rosana M.; Stammler, Hans-Georg; Mitzel, Norbert W.; Della Védova, Carlos O.
Abstract : CF3 C(O)SC(CH3 )3 species adopts a synperiplanar conformation with C s symmetry. After UV-visible broadband light irradiation in matrix conditions CF3 C(O)SC(CH3 )3 photoevolves to CF3 SC(CH3 )3 and CO. Abstract : S -( tert -Butyl)trifluorothioacetate, CF3 C(O)SC(CH3 )3, was prepared by condensation of CF3 C(O)Cl and (CH3 )3 CSH under vacuum conditions. The compound was isolated and properly characterized by using vibrational (infrared and Raman), UV-Vis and multinuclear NMR spectroscopy techniques and by mass spectrometry. The conformational preference and its crystal structure have been determined by means of FTIR spectroscopy (gas phase and Ar-matrix) and by X-ray diffraction. A charge density determination of X-ray diffraction (XRD) data of single crystals formed by in situ crystallization reveals the presence of solely a synperiplanar conformation ( syn form orientation of the CO double bond with respect to the S–C single bond) belonging to the C s point group of symmetry. Intermolecular CO⋯CO and CO⋯H–C interactions were detected in the crystal. Quantum-chemical calculations at the B3LYP/cc-pVTZ level of approximation reproduce the conformational preference and the experimental geometrical parameters fairly well. Vibrational information was obtained from Ar-matrix isolation FTIR and liquid Raman spectroscopy. Additionally, CF3 C(O)SC(CH3 )3 isolated in solid Ar at ca. 15 K was irradiated with UV-visible broadband light (200 ≤ λ ≤ 800 nm) and its photolysis products CF3 SC(CH3 )3 and CO were detected.